2000
DOI: 10.4049/jimmunol.164.10.5492
|View full text |Cite
|
Sign up to set email alerts
|

Induction of an Antigen-Specific CTL Response by a Conformationally Biased Agonist of Human C5a Anaphylatoxin as a Molecular Adjuvant

Abstract: A conformationally biased decapeptide agonist of human C5a anaphylatoxin (YSFKPMPLaR) was used as a molecular adjuvant in stimulating an Ag-specific CTL response against murine P815S target cells expressing an Ld-restricted CTL epitope of the hepatitis B surface Ag (HBsAg). Groups of BALB/c mice (H-2d) were immunized with aqueous solutions of the HBsAg CTL epitopes (IPQSLDSWWTSL and IPQSLDSWWTSLRR); the C5a agonist (YSFKPMPLaR); the C5a agonist and HBsAg CTL epitopes admixed (IPQSLDSWWTSL and IPQSLDSWWTSLRR + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
34
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 28 publications
6
34
0
2
Order By: Relevance
“…The immunologic results presented in this study are consistent with those observed with an EP54-containing vaccine to nicotine [15] and with a mechanism we proposed earlier to describe the molecular adjuvant properties of EP54 (YSFKPMPLaR) and its ability to induce Ag-specific Ab and cell-mediated immune responses [20][21][22][23][24]. Briefly, EP54 selectively interacts with C5aRs on antigen presenting cells (especially DCs) and induces the release of Th1 cytokines.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The immunologic results presented in this study are consistent with those observed with an EP54-containing vaccine to nicotine [15] and with a mechanism we proposed earlier to describe the molecular adjuvant properties of EP54 (YSFKPMPLaR) and its ability to induce Ag-specific Ab and cell-mediated immune responses [20][21][22][23][24]. Briefly, EP54 selectively interacts with C5aRs on antigen presenting cells (especially DCs) and induces the release of Th1 cytokines.…”
Section: Discussionsupporting
confidence: 76%
“…EP54 retains C5a-like immune stimulatory properties, but with significantly reduced C5a-like inflammatory properties [17][18][19][20]. The role of the molecular adjuvant EP54 in these vaccines is to target covalently attached Ags to and activate the Ag processing and presentation capacity of C5a receptor-bearing antigen presenting cells [21][22][23], particularly dendritic cells (DCs) [24].…”
Section: Introductionmentioning
confidence: 99%
“…C5a has also been demonstrated to have an influence in adaptive immune responses. In this regard, it has been shown to act as an adjuvant by enhancing the humoral response [15] and by promoting antigenspecific cytotoxic (CTL) responses [16].…”
Section: Introductionmentioning
confidence: 99%
“…There are a large number of successful animal studies; however, to date there are few human studies showing the successful induction of humoral and cellular immune responses (45). Adjuvants have been used to induce CTL responses to subunit or inactivated viruses (28,34,50,55). However, the discovery of adjuvants that are both safe and effective has proven to be a great challenge.…”
mentioning
confidence: 99%